FRI0562 Adverse events with the use of radiotherapy in patients with connective tissue diseases and cancer. (23rd January 2014) - Lopez-Olivo, M. A.; Martinez Lopez, J. A.; Tayar, J. H.; Bavineni, M.; Fulton, S.; Suarez-Almazor, M. E.
Abstract : Background: In the era of modern cancer management radiotherapy remains a cornerstone for the multi-modality curative treatment of cancer. Objectives: We review the evidence to identify crucial issues regarding the safety of use of radiotherapy in patients with malignancy and CTDs. Methods: We conducted a comprehensive search in the following electronic databases: MEDLINE, EMBASE, Web of Science, and The Cochrane Library from inception through December 2012. Our search strategy was restricted to human subjects and studies published in English, French, or Spanish. Study selection, data collection and quality assessment were independently performed by two pairs of investigators. Our primary outcome was safety including: (i) incidence of adverse events due to radiotherapy in CTD; (ii) effects of radiotherapy on underlying disease either flares or increased organ damage; and (iii) incidence of new CTD in patients receiving radiotherapy. Meta-analyses were performed when there were two or more studies with similar outcomes. Results: 47 publications met our inclusion criteria (8 retrospective cohorts and 39 case reports). Study quality raged from fair to moderate. 709 patients received radiation at curative doses. The age of the included patients ranged from 16-72. Radiation therapy was used for patients with CTDs including ankylosing spondylitis and Wegener's granulomatosis. Total lymphoid irradiation was used for patients with rheumatoid arthritis and lupus nephritis and systemic sclerosis. Regarding CTD induced after radiotherapy, there were 14 studies reporting 25 new CTD cases after cancer radiotherapy. Scleroderma was present in 18/25 patients and most cases were related to breast carcinoma 14/18. For patients who had both conditions (cancer and CTD), we found reports on 30 patients with dermatomyositis/polymyositis (30 with nasopharyngeal cancer), 15 patients with scleroderma (8 with breast cancer), 8 patients with systemic lupus erythematosus and (5 with breast cancer). There were not statistically significant differences in the risk of having acute or late adverse events in any type of CTD. However, patients with discoid lupus erythematosus had higher rates of severe acute adverse events (40% vs. 23%). Contrastingly, higher rates of severe late adverse events were reported in patients with scleroderma (25% vs. 45%) and rheumatoid arthritis (10.3% vs. 16.5%). There were no reports on flares from underlying CTD. Conclusions: We observed non-statistically significant increased rates of acute and late severe adverse events in patients with CTD undergoing radiotherapy. Although, radiotherapy is an essential component of cancer therapy, oncologists should be aware that patients with rheumatic diseases requiring radiotherapy as a part of the treatment regimen might be at a greater risk of developing severe adverse events. Acknowledgements: Dr. Suarez-Almazor has a K24 career award from the National Institute for Arthritis, Musculoskeletal and Skin Disorders (NIAMS). Disclosure of Interest: None Declared